Elections, news cycles, and attention to disasters. Issue 4 (7th August 2017) - Bright, Candace Forbes; Bagley, Braden
Abstract : Purpose: Political elections, especially presidential elections, have a tendency to overshadow other events, including disasters. Response to disasters during elections, such as Hurricane Matthew and the Baton Rouge flooding in 2016, are often dependent on attention given to them from the media, as well as prominent political figures and political candidates candidates. The purpose of this paper is to explore how election cycles affect government response to disasters and ultimately demonstrate the dependency of crisis communication on media agenda-setting for presenting saliency of disaster risk and needs. Design/methodology/approach: Responses from presidential candidates Donald Trump and Hillary Clinton, as well as President Barack Obama, in regards to the Baton Rouge flooding and Hurricane Matthew, were observed using media reports and social media accounts. These results were matched with key events from the presidential election timeline. Findings: There is a positive relationship between news exposure and attention, and also between attention and civic response. In regards to the 2016 presidential election, news coverage of the release of the Donald Trump-Billy Bush tape distracted national attention from the approach, landfall, and recovery of Hurricane Matthew. Information subsidies provided by the candidates directed the media agenda away from the needs of the communities and individuals impacted by these disasters. Originality/value: Disasters are often assumed to be value-free because they are "blind to politics." Here, it is argued that this was not the case in relation to these two disasters. Thus, the authors encouraged more research be conducted to clarify the impact that political elections have on strategic news coverage of disasters and ultimately on disaster response.